2021
DOI: 10.1590/0001-3765202120191526
|View full text |Cite
|
Sign up to set email alerts
|

Refinement as ethics principle in animal research: Is it necessary to standardize the Environmental enrichment in laboratory animals?

Abstract: The Environmental enrichment technique, although scientifi cally recognized for raising the level of animal welfare, has led to the questioning of its infl uence on the results of experimental research. Thus, the goal is to promote refl ection about the need for standardization of these procedures. For that, documents and experimental analysis were done, in order to quantify and characterize the types of environmental enrichment used and to evaluate the effect of that in the social behavior of Rattus norvegicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Studies focusing on laboratory animals were abundant, showing that the concern to improve the welfare of these animals is great since they are often used in biomedical research and the results of such research need to be reliable [ 41 , 42 , 43 ]. Some studies have already shown that low levels of welfare in these animals can generate dubious results in these studies [ 44 , 45 ]. The number of sample individuals used in both farm and laboratory environments is notably higher than in other environments, such as zoos, aquariums, shelters, and pets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on laboratory animals were abundant, showing that the concern to improve the welfare of these animals is great since they are often used in biomedical research and the results of such research need to be reliable [ 41 , 42 , 43 ]. Some studies have already shown that low levels of welfare in these animals can generate dubious results in these studies [ 44 , 45 ]. The number of sample individuals used in both farm and laboratory environments is notably higher than in other environments, such as zoos, aquariums, shelters, and pets.…”
Section: Discussionmentioning
confidence: 99%
“…Para ello, existen recursos que ayudan a determinar qué tipo de EA se debe aplicar (Baumans et al, 2010;Fischer et al, 2021). La Guía para el Cuidado y Uso de los Animales de Laboratorio, octava edición, 2011 (Guide for the Care and Use of Laboratory Animals); establece como objetivo principal del EA «mejorar el bienestar de los animales mediante la estimulación sensorial y motora» Para ello, se utilizan estructuras u otros recursos (EA de tipo físico y Social; (Baumans, 2005) que faciliten la expresión de comportamientos típicos de la especie y promuevan su bienestar psicológico y fisiológico reduciendo el estrés, la ansiedad (Bailoo et al, 2018;Bayne, 2018;Benefiel et al, 2005;Oatess et al, 2020); y ayuden en el aumento o control de peso, mejoras en ciertos parámetros inmunitarios (Marashi et al, 2004); en la memoria y el aprendizaje (Guan et al, 2021), incrementando el instinto y cuidado materno de las crías (Sparling et al, 2020); reduciendo la agresividad (Burrows et al, 2020), etc.…”
Section: Discusionunclassified
“…Organoid technology is a long-awaited substitute for animal experimentation. Several countries currently have animal experimentation restrictions in their animal research regulations, which implies that researchers must always work to decrease, improve, and replace animal experimentation (Olsson et al, 2007;Fischer et al, 2021). In the future, as there is advancement in organoid model technology with newer and more precise models being developed, the rationale for using animal experiments instead of organoid models may need to be articulated depending on the circumstances.…”
Section: Ethical Issues In the Research And Use Of Ipsc-based Organoi...mentioning
confidence: 99%